2012
DOI: 10.1636/hi12-23.1
|View full text |Cite
|
Sign up to set email alerts
|

Notes on the ecology and behavior of a subsocial spider Anelosimus baeza (Araneae: Theridiidae) in Mexico

Abstract: Subsocial spiders are located on the continuum between solitary species and social species and are characterized by extended maternal care, some cooperation in foraging and colony activities and dispersal in order to found new colonies. In the genus Anelosimiis (Araneae: Theridiidae), up to nine species are thought to be subsocial. One of these spiders, A. baeza Agnarsson (2006), is distributed across a large geographical range from Mexico to southern Brazil, and potential differences in behavior in different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Changes in the behaviour of spiders can be influenced by the decrease in temperature (Foelix, ). Several predators such as spiders (Perkins, Riechert, & Jones, ; Rao & Aceves‐Aparicio, ) and ants (Hoffman & Avilés, ; Purcell & Avilés, ) have been previously identified in Anelosimus colonies (Perkins et al., ; Powers & Avilés, ; Purcell & Avilés, ); for A. baeza, a subset of these have also been previously reported (Rao & Aceves‐Aparicio, ). Although night movements may reduce possible encounters with predators, we observed several pirate spiders (Araneae: Mimetidae) feeding on Anelosimus spiders during the night, and only a couple during the day.…”
Section: Discussionmentioning
confidence: 90%
“…Changes in the behaviour of spiders can be influenced by the decrease in temperature (Foelix, ). Several predators such as spiders (Perkins, Riechert, & Jones, ; Rao & Aceves‐Aparicio, ) and ants (Hoffman & Avilés, ; Purcell & Avilés, ) have been previously identified in Anelosimus colonies (Perkins et al., ; Powers & Avilés, ; Purcell & Avilés, ); for A. baeza, a subset of these have also been previously reported (Rao & Aceves‐Aparicio, ). Although night movements may reduce possible encounters with predators, we observed several pirate spiders (Araneae: Mimetidae) feeding on Anelosimus spiders during the night, and only a couple during the day.…”
Section: Discussionmentioning
confidence: 90%
“…There was no relationship between the number host spiders inside a nest and diversity of foreign spiders. Rao & Aceves-Aparicio (2012) found that larger Anelosimus baeza Agnarsson, 2006 nests had more diverse foreign associates. They speculated that colony failures in the sub-social spider A. baeza are linked to a larger number of foreign inhabitants.…”
Section: Discussionmentioning
confidence: 96%
“…Foreign arthropods that have been reported inside the nests as well as on the webs of social spider species belong to Theridiidae, Eresidae, Desidae and Dictynidae (nest associates: Griswold & Meikle 1987; Downes 1994; Perkins et al 2007; Rao & Aceves-Aparicio 2012; Fernandez-Fournier & Avilés 2018; web associates: Lubin & Robinson 1982; Bradoo 1989; Cangialosi 1990; Downes 1994; Rypstra & Binford 1995; Leborgne et al 2011; Straus & Aviles 2018). Although there are reports on foreign arthropods residing inside nests of Stegodyphus Simon, 1873 spiders (Bradoo 1972; Jackson 1987; Drisya-Mohan et al 2019), few have examined the nature of interactions between these foreign associates and their social spider hosts.…”
mentioning
confidence: 99%
“…Anelosimus arizona (Powers & Avilés, 2003), typically disperse very short distances, often within a few meters. baeza behaves differently and undergoes different phenology in different populations (Agnarsson, 2006;Rao & Aceves-Aparicio, 2012), suggesting that some subsocial 'species' may actually be species complexes. Reproductive isolation could lead to greater speciation.…”
Section: Consequences Of Subsociality (1) Dispersalmentioning
confidence: 99%
“…It has also been reported that An. baeza behaves differently and undergoes different phenology in different populations (Agnarsson, 2006;Rao & Aceves-Aparicio, 2012), suggesting that some subsocial 'species' may actually be species complexes. Speciation and extinction have been investigated in the cooperative social Anelosimus and Stegodyphus, which, because there is little migration among colonies, form reproductively isolated demes (Agnarsson et al, 2006a;Johannesen et al, 2007).…”
Section: Consequences Of Subsociality (1) Dispersalmentioning
confidence: 99%